NONLINEAR FINITE ELEMENT ANALYSIS FOR LARGE AEROSPACE VACUUM TANK - QIN Chao; TIAN ShiTao (Jixie qiangdu, 2016)
In other to simulate the contact relation between the body and the door of the large aerospace vacuum tank,propose a nonlinear finite element method by using the gap elements. Build the finite element model of a large aerospace vacuum tank by MSC. Patran and MSC. Nastran. Lead up the nonlinear contact elements to consider the contact,then take the strength analysis of the large aerospace vacuum tank in three conditions. Get the maximum clearance between the body and door are 0. 015mm、0. 017 mm and 0. 018 mm. Analyse the feasibility of using the gap elements to simulate the nonlinear contact. Prove that the simulation is effective. Provide a more exact method to analyse the strength of the large aerospace vacuum tank.